Analisis Penyusutan Aset Tetap Pada Hotel Mitra Amanah Balikpapan Tahun 2016 - GIOVANNY ZUSANA LAKBURLAWAL; Anis Rachma Utary; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Giovanny Zusana Lakburlawal, 2019. Analysis of depreciation of fixed assets in Balikpapan trustful Hotel Partners in 2016. Under the guidance of Supervisor I Ms. Anis Rachma Utari and Supervisor II Mr. Indra Suyoto Kurniawan. The purpose of this study is to determine the depreciation expense of fixed assets in 2016. The analysis tool used is the Straight Line method. Based on the results of the study It was found that our partners did not do the same things such as Furniture, Machinery, electronic equipment, etc. After doing that to the amount of profit of the Hotel. Depreciation expense recorded by the hotel amounted to Rp 128,105,263 after processing it into Rp 256,173,804. Income from profit per year profit and loss for Mitra Amanah Hotel in 2016 was Rp 660,295,408, after being processed into Rp 532,226,867.